Exposure to environmental contaminants and folic acid supplementation intergenerationally impact fetal skeleton development through the paternal lineage in a rat model - L. Charest, Phanie; Tessougue, Emmanuel; Lessard, Maryse; Herst, Pauline M.; Navarro, Pauline; Kimmins, Sarah; Trasler, Jacquetta M.; MacFarlane, Amanda J.; Benoit-Biancamano, Marie-Odile; Bailey, Janice L.; Dalvai, Mathieu (Frontiers in Toxicology, 2022)
Persistent organic pollutants (POPs) are ubiquitous in the environment, which is of concern since they are broadly toxic for wildlife and human health. It is generally accepted that maternal prenatal folic acid supplementation (FA) may beneficially impact offspring development, but it has been recently shown that the father's exposures also influence the health of his offspring. Bone is an endocrine organ essential for whole-body homeostasis and is susceptible to toxicants. Herein, we tested the hypotheses that prenatal paternal exposure to POPs induces developmental bone disorders in fetuses across multiple generations and that folic acid (FA) supplementation attenuates these disorders. We used a four-generation rat model, in which F0 founder females were divided into four treatment groups. F0 females were gavaged with corn oil or an environmentally-relevant POPs mixture and fed either a control diet (2 mg FA/kg), or FA supplemented diet (6 mg FA/kg) before mating and until parturition (four treatments in total). After the birth of the F1 litters, all F0 females and subsequent generations received the FA control diet. Staining with alcian blue and alizarin red S of male and female fetal skeletons was performed at Gestational Day 19.5. Paternal direct and ancestral exposure to POPs delayed bone ossification and decreased the length of long limb bones in fetuses. Maternal FA supplementation did not counteract the POPs-associated delayed fetal ossification and reduced long bone length. In conclusion, prenatal paternal POPs exposure causes developmental bone abnormalities over multiple generations, which were not corrected by maternal FA supplementation.